Clinical evaluation of selected Pharmacological Treatments used for Coronavirus (COVID-19) pandemic - altemimy, hasan mohammed (Journal of the Faculty of Medicine Baghdad, 2020)
Background: Coronavirus is an enveloped RNA virus, from the genus Betacoronavirus, that is distributed in birds, humans, and other mammals. WHO has named the novel coronavirus disease as COVID-19. Objective: We have conducted this review to focus on the studies that assessed the treatment efficacy and safety of Coronavirus (COVID-19) to describe its relation with the clinical outcomes of patients. Method: PubMed, was searched for studies on the clinical evaluation of selected currently used treatments for COVID-19. we included six studies about therapeutic activity of chloroquine/hydroxychloroquine, two case series about oseltamivir and three studies about lopinavir/ritonavir Results: some of studies have been demonstrated and approved for a wider use hydroxychloroquine for COVID-19, others concluded that there was insufficient evidence to offer any recommendation on the routine use of these drug in patients admitted to the intensive care unit (ICU). Other treatments have insufficient evidence to recommend the use (lopinavir-Ritonavir or oseltamivir) for COVID-19 outside of research studies. Conclusion: In order to determine their efficacy and safety for COVID-19, more adequately powered randomized clinical trials are required. Ideally, these studies should be double-blinded and conducted in a range of settings. Keywords: Covid-19, hydroxychloroquine, Azithromycin, Oseltamivir, lopinavir-Ritonavir